Development of non-adherent single cell culturing and analysis techniques on microfluidic devices - Viberg, Pernilla (Kansas State University, 2009)
Microfluidic devices have a wide variety of biological applications. My Ph.D. dissertation focuses on three major projects. A) culturing a non-adherent immortal cell line within a microfluidic device under static and dynamic media flow conditions; B) designing and fabricating novel microfluidic devices for electrokinetic injecting analytes from a hydrodynamic fluid; and C) using this novel injection method to lyse single non-adherent cells by applying a high electric field across the cell at a microfluidic channel intersection. There are several potential advantages to the use of microfluidic devices for the analysis of single cells: First, cells can be handled with care and precision while being transported in the microfluidic channels. Second, cell culturing, handling, and analysis can be integrated together in a single, compact microfluidic device. Third, cell culturing and analysis in microfluidic devices uses only extremely small volumes of culturing media and analysis buffer. In this dissertation a non-adherent immortal cell line was studied under static media flow conditions inside a CO[subscript]2 incubator and under dynamic media flow conditions in a novel portable cell culture chamber. To culture cells they must first be trapped on a microfluidic device. To attempt to successfully trap cells, three different types of cellular traps were designed, fabricated and tested in polydimethylsiloxane (PDMS)-based microfluidic devices. In the first generation device, cubic-shaped traps were used. After 48 h of culturing in these devices the cell viability of 79 [plus or minus] 6 % (n = 3). In the second generation device, circular wells with narrow connecting channels were employed. However, after 12 h of culturing, no viable cells were found. While the second generation device was not capable of successfully culturing cells, it did demonstrate the importance of culturing under dynamic conditions which lead to next design. The third generation microfluidic device consisted of hydrodynamic shaped traps that were used to culture the cells in a less confined environment. The cell viability after 12 h in this design was 29 [plus or minus] 41% (n = 3). In addition to cell trapping, a novel electrokinetic injection method was developed for injecting analytes from a hydrodynamic flow into a separation channel that was followed by an electrokinetic separation. As the hydrodynamic flow could introduce some excess band broadening in the separation, the actual band broadening of an analyte was measured for different channel depths and hydrodynamic fluid flow rates. The results consistently showed that the separations performed on these devices were diffusion limited. Finally, using this novel injection method, single cell lysis was performed by applying a high voltage at the microfluidic channel intersection. The results of these studies may eventually be applied to help answer some fundamental questions in the areas of biochemistry and pharmaceutical science.
Keywords: Microfluidic Devices; Cell Culturing; PDMS; Diffusion Coefficient; Chemistry, Analytical (0486)